Does Artificial Intelligence Have an Impact on Monetary Policy Effectiveness in Indonesia? - Anisa Syahidah Mujahidah; Anisa Syahidah Mujahidah (Bank Indonesia, 2026)
The study empirically investigates the implications of AI Readiness, Broad Money, and political stability for monetary policy effectiveness, as measured by a composite index. The study uses robust fixed-effect panel data estimation techniques to analyse data from 19 OIC member countries between 2019 and 2023, with a focus on Indonesia. The results show that AI readiness and political stability have a substantial positive impact on monetary policy effectiveness in Indonesia, whereas Broad Money has a significant adverse impact. These findings offer relevant policy implications for AI transformation in the financial sector, particularly for effective monetary policy. These findings establish a relationship between the quest for high-quality institutions, defined by the readiness of AI implementation, political stability, and stable broad money. The study adds to a recent body of literature on the impact of AI and other variables on the efficiency of monetary policy.